Regulating Political Parties : European Democracies in Comparative Perspective - Napel, H.-M. T. D. ten; Biezen, Ingrid van (Book collections on Project MUSE., 2016)
The essays that make up Regulating Political Parties were first developed as part of an international symposium at Leiden University focusing on party law. Together, the contributions analyze the regulation of political parties within and beyond Europe from interdisciplinary and comparative perspectives. Addressing both conceptual issues and recent empirical findings, Regulating Political Parties is a valuable examination of an often-overlooked aspect of politics and will be useful for not only scholars, but also legal and political practitioners.